Relatedness of tetracycline resistance plasmids among species of coagulase-negative staphylococci. - Cooksey, R C (1985)
Four isolates of Staphylococcus aureus and 98 isolates of coagulase-negative staphylococci representing six species all obtained from endocervical cultures were examined for antimicrobial susceptibility and for the presence of plasmids. More than 80% of the isolates were susceptible to each of 12 antimicrobial agents tested, whereas only 33% were susceptible to penicillin G, 30% were susceptible to cadmium chloride, and 41% were susceptible to tetracycline. Although no species-related susceptibility or plasmid patterns were detected, 77 isolates contained at least one plasmid and 43 contained a plasmid similar in mass to a 2.7-megadalton tetracycline resistance plasmid previously reported in staphylococci. Association of tetracycline resistance with plasmids of this size in four species was determined from curing experiments. No plasmids homologous with the tetracycline resistance locus of the Escherichia coli plasmid pBR322 were found among 11 isolates examined by DNA hybridization. Homology with a 2.7-megadalton plasmids (pRC701) from an endocervical isolate of S. aureus, however, was apparent for 2.7-megadalton plasmids harbored by six isolates as well as with larger plasmids harbored by three isolates. Restriction analysis revealed that pRC701 shared structural identity with two plasmids of a similar mass from two species of coagulase-negative staphylococci as well as with a previously characterized tetracycline resistance plasmid originating in S. aureus.